Breaking Textbook Barriers: PowToon Videos in Engaging ICT Learning for Young EFL Learners - Minarni, Fitria; Mustofa, Mutmainnah; Nursafira, Mutia Sari (Universitas Lancang Kuning, 2023)
The significant interest in the development and integration of information and communication technologies (ICT) in the field of education is still marked with an unequal level of performance in many areas. This research explores the researcher-teacher collaboration of creating and using PowToon video in teaching English to achieve the mission of elevating the ICT competence of teachers and students in schools, especially in areas that are underdeveloped or far from the central government. The participants of the study include the sole English teacher of SD Kartika VI-7 Malang and twenty students in the fifth grade. Through four steps (analysing, designing, implementing, evaluating), this descriptive qualitative study collected data from classroom observation, teacher interview, expert analysis of the developed media, and short evaluation questionnaire. Results from the analysis stage confirmed the preliminary results of the English class’s minimal ICT usage. The design stage is where the researchers and the teacher worked together to adapt the textbook materials into interesting PowToon video for the students. The implementation stage is where the teacher used the video validated by three experts of material, media, and language. Finally, the media’s effectiveness is evaluated based on the questionnaire responses given by the students. The research concludes that the validation process of the PowToon ascertained its quality for effective English instruction to motivate student engagement. Although neither PowToon video nor its implementation is particularly new, they are novel, effective, and—arguably most importantly—friendly teaching media for classrooms that have yet to adapt with the rapid technological world.